1998
DOI: 10.1046/j.1469-8137.1998.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of ectomycorrhizal and non‐mycorrhizal Scots pine (Pinus sylvestris) seedlings to a generalist insect herbivore, Lygus rugulipennis, at two nitrogen availability levels

Abstract: We tested how nitrogen availability affects suitability of ectomycorrhizal (ECM) and non‐mycorrhizal Pinus sylvestris (L.) for a polyphagous insect herbivore. Seedlings grown on sterile agar at two N levels, were infected or not with the ECM fungus Cenococcum geophilum (Sow.) Ferd. & Winge. Ultrastructural observations showed that C. geophilum formed well‐developed ectomycorrhizas in pine roots. After mycorrhizal establishment, oviposition preference of the polyphagous tarnished plant bug (Lygus rugulipennis P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 33 publications
(46 reference statements)
4
36
2
Order By: Relevance
“…The effect of fertilization on terpene concentrations was not wholly clear (trends but not significant). Several previous studies have found no relation between terpene concentrations and nutrient addition (Manninen et al 1998;Muzika et al 1989). In the present experiment, P fertilization had no significant effect on its own, but when there was P fertilization and drought effect, which was highly significant in P. halepensis plants for the total terpene contents, and for the principal individual terpenes: a-pinene and D 3 -carene.…”
Section: Discussionmentioning
confidence: 96%
“…The effect of fertilization on terpene concentrations was not wholly clear (trends but not significant). Several previous studies have found no relation between terpene concentrations and nutrient addition (Manninen et al 1998;Muzika et al 1989). In the present experiment, P fertilization had no significant effect on its own, but when there was P fertilization and drought effect, which was highly significant in P. halepensis plants for the total terpene contents, and for the principal individual terpenes: a-pinene and D 3 -carene.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have shown that mycorrhizae decrease the abundance and performance of herbivores (Gehring & Whitham, 2002;Vicari et al, 2002;Wamberg et al, 2003). Other studies have shown that mycorrhizae had no effect (Gange & Nice, 1997;Manninen et al, 1998) or even a positive effect on herbivore abundance and performance (Borowicz, 1997;Goverde et al, 2000). Many of the studies that have investigated the effects of mycorrhizae on plant-insect interactions have been conducted in a laboratory setting, or have involved removal of mycorrhizae with fungicides (reviewed in Gange, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…The additional nutrients provided by these symbionts change plant tissue quality which, in turn, can influence plantherbivore interactions. However, little research has addressed effects of symbionts that co-occur in the habitat on insect-plant relationships (Briggs 1990;Gehring and Whitham 1994;Manninen et al 1998).…”
Section: Introductionmentioning
confidence: 99%